Analysis of Carbamate and Organophosphate Insecticides Residue by Rapid Bioassay Pesticide Residue in Vegetables in Bagmati Province Nepal - Bhusal, Anish; Regmi, Sheershak; Gairhe, Shristi; Khanal, Dipak (Nepalese Journal of Agricultural Sciences, 2025)
The excessive use of chemicals, specifically the carbamates and organophosphates, results in pesticide residues in vegetables posing a significant risk and issue of causing both acute and chronic diseases. This study aimed to analyse the pesticide residue levels in vegetables grown in seven districts of Bagmati Province, of Nepal, using Rapid bioassay of pesticide residue (RBPR) technique. The acetyl cholinesterase (AChE) inhibition percentage of spinach, potatoes, and sword beans displayed consistently high inhibition percentages across 888 vegetable samples tested. One of spinach sample turned out to be unsafe for consumption since it exceeded a 45% inhibition threshold. Furthermore, higher pesticides residues were observed in some of the major vegetables like potato, capsicum, sword beans as compared to others. Samples from Bhaktapur district showed the highest carbamate and organophosphate inhibition percentage level, while those from Lalitpur displayed the lowest as compared to the other districts. As per the findings, producer must stick to follow proper pesticide use and follow the practices such as waiting period, in order to safeguard the consumers. This study demonstrates the significance of RBPR as a cost-effective and easy method for timely evaluation of pesticide residues in easily perishable commodities.